Responder
\[
\overrightarrow{A B} = -\underline{b}, \quad \overrightarrow{C D} = -\underline{b}, \quad \overrightarrow{B E} = -\underline{b} - 2\underline{a}
\]
Solución
To express the vectors \( \overrightarrow{A B}, \overrightarrow{C D} \), and \( \overrightarrow{B E} \) in terms of \( \underline{a} \) and \( \underline{b} \), we first need to understand the geometry of the regular hexagon ABCDEF.
1. **Understanding the Hexagon:**
- A regular hexagon can be inscribed in a circle, and its vertices can be represented in a coordinate system.
- Let's place the hexagon in the Cartesian plane with the following coordinates:
- \( A(1, 0) \)
- \( B\left(\frac{1}{2}, \frac{\sqrt{3}}{2}\right) \)
- \( C\left(-\frac{1}{2}, \frac{\sqrt{3}}{2}\right) \)
- \( D(-1, 0) \)
- \( E\left(-\frac{1}{2}, -\frac{\sqrt{3}}{2}\right) \)
- \( F\left(\frac{1}{2}, -\frac{\sqrt{3}}{2}\right) \)
2. **Given Vectors:**
- \( \overrightarrow{BC} = \underline{b} \)
- \( \overrightarrow{FC} = 2\underline{a} \)
3. **Finding the Vectors:**
- We can express the vectors in terms of the coordinates of the points.
### Step 1: Calculate \( \overrightarrow{A B} \)
\[
\overrightarrow{A B} = \overrightarrow{B} - \overrightarrow{A} = \left(\frac{1}{2}, \frac{\sqrt{3}}{2}\right) - (1, 0) = \left(-\frac{1}{2}, \frac{\sqrt{3}}{2}\right)
\]
### Step 2: Calculate \( \overrightarrow{C D} \)
\[
\overrightarrow{C D} = \overrightarrow{D} - \overrightarrow{C} = (-1, 0) - \left(-\frac{1}{2}, \frac{\sqrt{3}}{2}\right) = \left(-\frac{1}{2}, -\frac{\sqrt{3}}{2}\right)
\]
### Step 3: Calculate \( \overrightarrow{B E} \)
\[
\overrightarrow{B E} = \overrightarrow{E} - \overrightarrow{B} = \left(-\frac{1}{2}, -\frac{\sqrt{3}}{2}\right) - \left(\frac{1}{2}, \frac{\sqrt{3}}{2}\right) = (-1, -\sqrt{3})
\]
### Expressing in terms of \( \underline{a} \) and \( \underline{b} \)
Now, we need to express these vectors in terms of \( \underline{a} \) and \( \underline{b} \).
1. From the given \( \overrightarrow{BC} = \underline{b} \), we can find \( \overrightarrow{AB} \) and \( \overrightarrow{CD} \) in terms of \( \underline{b} \):
- Since \( \overrightarrow{BC} = C - B \), we can express \( \overrightarrow{AB} \) as:
\[
\overrightarrow{AB} = -\underline{b}
\]
2. For \( \overrightarrow{CD} \):
- Since \( \overrightarrow{CD} = D - C \), we can express it as:
\[
\overrightarrow{CD} = -\underline{b}
\]
3. For \( \overrightarrow{BE} \):
- Since \( \overrightarrow{FC} = 2\underline{a} \) and \( \overrightarrow{BE} = E - B \), we can express it as:
\[
\overrightarrow{BE} = -\underline{b} - 2\underline{a}
\]
### Final Expressions
Thus, the vectors in terms of \( \underline{a} \) and \( \underline{b} \) are:
- \( \overrightarrow{A B} = -\underline{b} \)
- \( \overrightarrow{C D} = -\underline{b} \)
- \( \overrightarrow{B E} = -\underline{b} - 2\underline{a} \)
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución